Physicochemical properties of harpagoside and its in vitro release from Harpagophytum procumbens extract tablets - Chrubasik, Sigrun; Sporer, Frank; Dillmann-Marschner, Ruth; Wink, Michael (Phytomedicine, 2000)
The objective of this investigation was to characterize the active-component harpagoside of Harpagophytum extract from a physico-chemical perspective and to determine its in-vitro release from tablets according to DAB 1996. It was found that both pure harpagoside and harpagoside in Harpagophytum extract have an octanol-water distribution coefficient of approximately 4 which is neither dependent on temperature nor on pH. The mean harpagoside content in Harpagophytum tablets of Batch 9102 was 16.4 mg (S.D. 0.2; S.E. 0.03). Related to a tablet weight of 365 mg (100%), this corresponds to a haragoside content of 4.5% (S.D. 0.049; S.E. 0.006). On average the tablets disintegrate after 18 +/- 3 minutes (mean +/- SD). The tablets taken from Batch 9102 released the active component harpagoside well, with a t50 of 13.5 min, a t90 of 23 min and a t95 of 25 min in relation to 16.5 mg of harpagoside per dose. Harpagoside content decreased by about 10% in artificial gastric fluid within a period of 3 hours and remained stable in artificial intestinal fluid for a period of 6 hours.